Dataset of Grey plover (Pluvialis squatarola) diet composition on the SW Black Sea coast using DNA metabarcoding - Liliana V. Vassileva; Lyudmila Lozanova; Martin Marinov; Jérôme Morinière; Boyko Neov; Boris Nikolov; Nikolay Simov; Stefania Klayn (Biodiversity Data Journal, 2025)
Wader populations have been declining globally due to widespread anthropogenic habitat degradation and loss. In this context, food quality and availability at migration stop-over sites is crucial for wader migration success.We studied the diet composition and preferences of the Grey plover (Pluvialis squatarola) at a stop-over site on the Black Sea-Mediterranean Flyway - Pomorie Lake, SW Black Sea coast, Bulgaria - through DNA metabarcoding of faeces. The study aimed to determine the bird's feeding strategy, coastal habitat use and possible seasonal variations as a result of local prey availability.The dataset includes new data on Grey plover (Pluvialis squatarola) prey items on the south-western Black Sea coast, Bulgaria. The diet composition data provides valuable insights on coastal biodiversity in the area as "sampled" by this generalist invertivore and contributes to the knowledge of Grey plover prey choice and habitat use in a little-studied microtidal marine region.